Long-term performance of the healed mortar with polymer containing phosphazene after exposed to sulfate attack - Tanyildizi, Harun (Elsevier Sci Ltd, 2018)
In this study, mortar samples were exposed to sulfate attack for 1 year and then healed with the polymer that contains phosphazene. After this healing, the microstructure and mechanical properties of these mortars were investigated. In the experimental work, the percentage of phosphazene in the monomer (0, 1%, 2%, 3% and 4%), the curing time (30, 60, 90, 180 and 365 days), the cement dosage (300, 350, 400, 450 and 500 kg/m(3)) and percentage of sulfate solution (0%, 1%, 2%, 4% and 6%) were selected as experimental parameters. Due to the high number of experimental parameters, experiments were reduced using the Taguchi L-25 (5(6)) orthogonal array as the test plan. After the design of the experiment, 50 x 50 x 50 mm cubes and 25 x 25 x 285 mm prismatic samples were prepared. The produced samples were exposed to the sulfate attack for the predetermined curing times. The samples were dried at 105 5 degrees C for 24 h after sulfate attack Following this procedure, the monomer containing phosphazene was impregnated to samples at atmospheric conditions for 24 h. 1% benzoyl peroxide was used as the monomer initiator. The samples were heated to 60 degrees C for 4 h to polymerize the monomers. The compressive strength, weight changes and length changes of mortar specimens healed using polymer containing phosphazene after sulfate attack were investigated. Furthermore, SEM, EDX and XRD analyzes were conducted on the samples. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Mortar; Sulfate attack; Phosphazene; Polymer; Microstructure